Internationalizing management system in Sabah Port Sdn Bhd / Sharidan Joe - Joe, Sharidan (2010)
This is entitled "Internationalizing Management System in Sabah Ports Sdn. Bhd". SPSB management is handed by locally. This style management system must change if possible. It because the performance of Sabah Ports is far behind compare with the other port such as Singapore and Penang Port. This company has potential to become competitiveness in industry port services. The reason is geography area of Sabah states is suitable and passage way for international trade and shipping. Furthermore is situation economy and investment in Sabah is in very good condition. Other than that is the merchant which sent and receive their goods to Sabah has alternative than using Sabah Ports. There are using other mode of transportation, nearest ports as well as may in future time using POIC port in Lahad Datu if this port will provide handling the cargos. So that SPSB must take this opportunity and avoid this threat to maximize their profitability as well as become competitiveness in their industry by change their management system style to internationalize it.